Favreina carpatica n. ichnosp. (crustacean microcoprolite) from the Middle Jurassic of Rucar-Bran Zone (southern Carpathians, Romania) - Senowbari-Daryan, Baba; Lazăr, Iuliana; Bucur, Ioan I. (Rivista Italiana Di Paleontologia E Stratigrafia, 2013)
The new crustacean microcoprolite, Favreina  carpatica ,is described from the Middle Jurassic of Rucăr-Bran zone, South Carpathians. It is the ichnospecies with the highest number (about 280) of longitudinally arranged canals pasing through the rod-shaped microcoprolite. Favreina carpatica was found in reddish to brown-carbonate sediments.
UnivIS-Import:2017-11-07:Pub.2013.nat.dgeo.IGM.LP.favrei
Keywords: Crustacean; Favreina; Microcoprolite; Middle Jurassic; Rucǎr-Bran zone; Southern Carpathians